Impacts of Ecology on Theories of Criminality - Batanjski, Vera (Zbornik Instituta za kriminološka i sociološka istraživanja, 2011)
Studying criminality, scientists of social sciences have used the knowledge of the natural sciences, such as biology and its scientific disciplines. Ecological theory has emerged as an attempt to explain the occurrence of criminality by using the knowledge of ecology and the relationship between competition and symbiosis, and the impacts that physical and social environments have on humans. Observing the relationships that exist between animal populations in natural ecosystems, was used to compare the behavior of people in the city. This is how the Chicago (Ecological) School appeared, whose representatives, among others, were: R. E. Park and E. W. Burgess. Starting from Darvin’s "struggle for survival", they identified five radially arranged zones in the city of Chicago, very similar to the forest ecosystem, and the validity, weaknesses and usefulness of this concept are the subject of this paper.